2020
DOI: 10.1287/ijoo.2019.0021
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Approach to the Capacitated Vehicle Routing Problem with Uncertain Costs

Abstract: We investigate a robust approach for solving the capacitated vehicle routing problem (CVRP) with uncertain travel times. It is based on the concept of K-adaptability, which allows one to calculate a set of k feasible solutions in a preprocessing phase before the scenario is revealed. Once a scenario occurs, the corresponding best solution may be picked out of the set of candidates. The aim is to determine the k candidates by hedging against the worst-case scenario, as is common in robust optimization. This ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Nevertheless the run-time increases with the dimension and with which is mainly due to the increasing run-time of Algorithm 1. Here with higher dimension the calculation time of the deterministic problem increases, while with increasing the number of iterations of Algorithm 1 increases which was already observed in [30,42]. Another positive observation is that the root gap is very small in general, mostly 0 and never larger than 34% .…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Nevertheless the run-time increases with the dimension and with which is mainly due to the increasing run-time of Algorithm 1. Here with higher dimension the calculation time of the deterministic problem increases, while with increasing the number of iterations of Algorithm 1 increases which was already observed in [30,42]. Another positive observation is that the root gap is very small in general, mostly 0 and never larger than 34% .…”
supporting
confidence: 60%
“…We only require an arbitrary procedure which returns an optimal solution for the given scenario. In [42] the authors applied the latter algorithm to the min-max-min robust capacitated vehicle routing problem and showed that on classical benchmark instances the number of iterations of Algorithm 1 is significantly smaller than the dimension of Z in general.…”
Section: Proposition 1 If All First-stage Variables Are Fixed Then (Lb) Is Equal To the Exact Objective Value Of The Fixed First-stage Somentioning
confidence: 99%
See 1 more Smart Citation
“…Using the min-max-min approach a small number of transportation-plans can be calculated in advance to decide which long-term decision have to be made and to prepare all employees. Another example, taken from Eufinger et al (2018); Subramanyam et al (2017), considers a parcel service delivering to the same customers every day, i.e. X is the set of feasible solutions of the vehicle routing problem.…”
Section: Introductionmentioning
confidence: 99%
“…Besides,[59][60][61] investigated the Cumulative CVRP in which the objective is to minimize the sum of arrival times at customers rather than total routing cost or distance.The authors concluded that this problem constitutes a good way to model situations where arrival time at customers is very important such as after natural disasters.Moreover, Lei et al[62] and Eufinger et al[63] incorporated some uncertainty in their studies; the former authors developed a neighborhood search heuristic to solve the problem with stochastic demands while the latter authors came up with a robust approach that takes travel times uncertainty into account. Results confirmed the superiority of the proposed heuristics over an alternative solution approaches.…”
mentioning
confidence: 99%